2010
DOI: 10.1111/j.1538-7836.2010.03882.x
|View full text |Cite
|
Sign up to set email alerts
|

Management of anticoagulation following central nervous system hemorrhage in patients with high thromboembolic risk

Abstract: To cite this article: Hawryluk GWJ, Austin JW, Furlan JC, Lee JB, OÕKelly C, Fehlings MG. Management of anticoagulation following central nervous system hemorrhage in patients with high thromboembolic risk. J Thromb Haemost 2010; 8: 1500-8. Summary. Background:Patients who present with central nervous system (CNS) hemorrhage while on anticoagulation (AC) for thromboembolic (TE) risk factors are a challenge to manage. Objective: We sought to inform decisions surrounding the timing and intensity of AC resumption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
56
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 61 publications
1
56
1
2
Order By: Relevance
“…16 In our study there was a trend toward increased thromboembolism in patients on any preoperative AT (2.60% vs 0.81%), though this was not statistically significant. Patients on clopidogrel had the most thromboembolic complications; this may have been due partly to the cessation of clopidogrel earlier than ASA or warfarin.…”
contrasting
confidence: 39%
“…16 In our study there was a trend toward increased thromboembolism in patients on any preoperative AT (2.60% vs 0.81%), though this was not statistically significant. Patients on clopidogrel had the most thromboembolic complications; this may have been due partly to the cessation of clopidogrel earlier than ASA or warfarin.…”
contrasting
confidence: 39%
“…A recently published systematic review with 492 patients concluded that anticoagulation may be resumed after 72 hours. 17 This review included a large number of single-case reports with a high risk for bias toward successful cases, and the authors considered all anticoagulants of any dose together. The hitherto largest cohort included 141 patients, of whom 35 patients resumed warfarin; however, the follow-up was only 30 days, which may explain why no recurrent intracranial hemorrhage was observed.…”
Section: Discussionmentioning
confidence: 99%
“…This increases the rate of recurrent thromboembolism at least in high-risk patients. 4 Compared with vitamin K antagonists (VKA), such as warfarin or phenprocoumon, new oral anticoagulants, such as the direct thrombin inhibitor dabigatran etexilate (DE), exhibit reduced rates of intracranial hemorrhage, 5,6 indicating a potentially better benefit/risk profile for stroke prevention.…”
mentioning
confidence: 99%